Mechanisms of PTPσ-Mediated Presynaptic Differentiation - Bomkamp, Claire; Padmanabhan, Nirmala; Karimi, Benyamin; Ge, Yuan; Chao, Jesse T.; Loewen, Christopher J. R.; Siddiqui, Tabrez J.; Craig, Ann Marie (Frontiers in Synaptic Neuroscience, 2019)
Formation of synapses between neurons depends in part on binding between axonal and dendritic cell surface synaptic organizing proteins, which recruit components of the developing presynaptic and postsynaptic specializations. One of these presynaptic organizing molecules is protein tyrosine phosphatase σ (PTPσ). Although the protein domains involved in adhesion between PTPσ and its postsynaptic binding partners are known, the mechanisms by which it signals into the presynaptic neuron to recruit synaptic vesicles and other necessary components for regulated transmitter release are not well understood. One attractive candidate to mediate this function is liprin-α, a scaffolding protein with well-established roles at the synapse. We systematically mutated residues of the PTPσ intracellular region and used the yeast dihydrofolate reductase protein complementation assay to screen for disrupted interactions between these mutant forms of PTPσ and its various binding partners. Using a molecular replacement strategy, we show that disrupting the interaction between PTPσ and liprin-α, but not between PTPσ and itself or another binding partner, caskin, abolishes presynaptic differentiation. Furthermore, phosphatase activity of PTPσ and binding to extracellular heparan sulfate proteoglycans are dispensable for presynaptic induction. Previous reports have suggested that binding between PTPσ and liprin-α is mediated by the PTPσ membrane-distal phosphatase-like domain. However, we provide evidence here that both of the PTPσ phosphatase-like domains mediate binding to liprin-α and are required for PTPσ-mediated presynaptic differentiation. These findings further our understanding of the mechanistic basis by which PTPσ acts as a presynaptic organizer.